Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\{ x_n \}_n$ be a sequence of real numbers. Suppose $ \lim_{n \to \infty}x_n=a.$

Show that
$$\lim_{n \to \infty} \frac{x_1+x_2+...+x_n}{n}=a$$

As it is my first proof I'm not really sure whether I am allowed to do the following steps:

$$S_n = \sum_{i=1}^{n}{x_n} = S_{n-1}+x_n$$ Therferore we get $x_n=S_n-S_{n-1}$

Taking $\lim_{n \to \infty} x_n=\lim_{n \to \infty}(S_n-S_{n-1})=\lim_{n \to \infty}S_n-\lim_{n \to \infty}S_{n-1}$

We know that: $\lim_{n \to \infty} x_n=a$ and we also know that $S_{n-1}=S_{n-2}+x_{n-1}$

Therefore we get: $a=\lim_{n \to \infty}S_n-\lim_{n \to \infty}S_{n-2}-\lim_{n \to \infty}x_{n-1}$

Now $\lim_{n \to \infty}x_{n-1}=\lim_{n \to \infty}x_{n}=a$ and $a=\lim_{n \to \infty}S_n-\lim_{n \to \infty}S_{n-2}-a$

Repeating these steps we get: $a=\lim_{n \to \infty}S_n-\lim_{n \to \infty}S_{n-n}-(n-1)a=\lim_{n \to \infty}S_n-\lim_{n \to \infty}S_{0}-(n-1)a$

As $\lim_{n \to \infty}S_{0}=0$ we get $a=\lim_{n \to \infty}S_n-(n-1)a$ or if we rearrange $n*a=\lim_{n \to \infty}S_n$

Using the product rule for limits we get: $a=\frac{\lim_{n \to \infty}S_n}{n}=\lim_{n \to \infty}\frac{S_n}{n}$ q.e.d.

Is this proof consistent and complete?

share|cite|improve this question
What does the limit in the first line refer to? It says $\lim_{n\to\infty}=a$. Do you mean $\lim_{n\to\infty}x_n=a$? – hejseb Nov 29 '13 at 8:26
The existence of limit of $S_n$ is not guaranteed. So, you cannot split the limit in $x_n=S_n-S_{n-1}$. – i707107 Nov 29 '13 at 8:27
@hejseb yes I mean $ \lim_{n \to \infty}x_n=a.$ – Exclusive92 Nov 29 '13 at 8:36
up vote 0 down vote accepted

As mentioned in answer from Aryabhata your method of proof has serious errors. I am providing a standard proof below.

Let $y_{n} = x_{n} - a$ then $\lim_{n \to \infty}y_{n} = 0$ and $$\lim_{n \to \infty}\frac{y_{1} + y_{2} + \cdots + y_{n}}{n} = \lim_{n \to \infty}\frac{x_{1} + x_{2} + \cdots + x_{n}}{n} - a$$ We will establish that $$\lim_{n \to \infty}\frac{y_{1} + y_{2} + \cdots + y_{n}}{n} = 0$$ and this will solve our problem. Invoking a new sequence $y_{n}$ tending to zero simplifies some of the logic below in a minor way.

Let $\epsilon > 0$ be arbitrary. Since $\lim_{n \to \infty}y_{n} = 0$, we have a positive integer $m$ such that $|y_{n}| < \epsilon$ whenever $n > m$. Let $M = \max\{|y_{1}|, |y_{2}|, \ldots, |y_{m}|\}$. Now we can see that

$\displaystyle \begin{aligned}\left|\frac{y_{1} + y_{2} + \cdots + y_{n}}{n}\right| &= \left|\frac{y_{1} + y_{2} + \cdots + y_{m} + y_{m + 1} + \cdots + y_{n}}{n}\right|\\ &\leq \left|\frac{y_{1} + y_{2} + \cdots + y_{m}}{n}\right| + \left|\frac{y_{m + 1} + \cdots + y_{n}}{n}\right|\\ &\leq \frac{|y_{1}| + |y_{2}| + \cdots + |y_{m}|}{n} + \frac{|y_{m + 1}| + |y_{m + 2}| + \cdots + |y_{n}|}{n}\\ &\leq \frac{m}{n}\cdot M + \frac{n - m}{n}\epsilon\end{aligned}$

In the above the value of $m$ is dependent on $\epsilon$ and value $M$ depends on $m$ so as far as the variable $n$ is concerned we can treat $m, M$ as constants depending on $\epsilon$. If $n \to \infty$ then $\left(\dfrac{m}{n}\cdot M + \dfrac{n - m}{n}\epsilon\right) \to \epsilon$. It follows that there is a positive integer $p$ such that $$\left|\frac{y_{1} + y_{2} + \cdots + y_{n}}{n}\right| \leq \epsilon$$ for $n > p$. This means that $$\lim_{n \to \infty}\frac{y_{1} + y_{2} + \cdots + y_{n}}{n} = 0$$

If you read the above proof carefully you will find that we have split $(y_{1} + y_{2} + \cdots + y_{n})/n$ into two parts. In one part the terms are not small but bounded and the number of terms is fixed. Considering the denominator $n$ this part tends to zero as $n \to \infty$. In the other part the number of terms depends on $n$ and becomes infinite as $n \to \infty$, but each term itself is small (less than $\epsilon$) so that the whole part is less than $\epsilon$. It follows that the expression $(y_{1} + y_{2} + \cdots + y_{n})/n$ is small when $n \to \infty$.

share|cite|improve this answer
Thank you very much for your detailed solution! – Exclusive92 Nov 29 '13 at 11:44
@Exclusive92: in case you like the solution you should accept/upvote the answer :) – Paramanand Singh Nov 29 '13 at 12:17

The proof is quite wrong and almost nonsensical (Sorry!).

1) You cannot assume $\lim_{n \to \infty} S_n$ exists.

2) Since $n$ is the variable which tends to infinity, you cannot repeat $n$ times like that and get it out of the limit.

3) The statement $na = \lim_{n \to \infty} S_n$ is nonsensical.

share|cite|improve this answer
Okay I I can see that. Could you give me a hint on how to tackle this proof? – Exclusive92 Nov 29 '13 at 8:44
@Exclusive92: This has appeared multiples on this site. Try searching for it. – Aryabhata Nov 29 '13 at 8:49

You can assume $(x_n) \to 0$ WLOG, since you can look at $x_n' = x_n - a$ else; this will allow you to even tackle only $x_n \geq 0$ (why?) and then proceed with a lot less restraints.

share|cite|improve this answer
Thank you very much! – Exclusive92 Nov 29 '13 at 11:44
@Exclusive92 Happy to help. If this solved your question, please mark it as answered. If not, feel free to ask for further explanation. – AlexR Nov 29 '13 at 11:57

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.